Volume 3: Heat Transfer; Electric Power; Industrial and Cogeneration 1999
DOI: 10.1115/99-gt-125
|View full text |Cite
|
Sign up to set email alerts
|

Blade Heat Transfer Measurements and Predictions in a Transonic Turbine Cascade

Abstract: Detailed heat transfer measurementa and predictions are given for a turbine rotor with 136° of turning and an axial chord of 12.7 cm. Data were obtained for inlet Reynolds numbers of 0.5 and 1.0 × 106, for isentropic exit Mach numbers of 1.0 and 1.3, and for inlet turbulence intensities of 0.25% and 7.0%. Measurements were made in a linear cascade having a highly three-dimensional flow field resulting from thick inlet boundary layers. The purpose of the work is to provide benchmark quality data for three-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The vortices lift off the end-wall and approach the 25% span. Previous measurements showed that the vortices exit the turbine blade at 50% midspan Giel et al [15]. This result is obtained by experimental measurements and confirmed by the numerical calculations.…”
Section: Grid Independence Studysupporting
confidence: 74%
See 2 more Smart Citations
“…The vortices lift off the end-wall and approach the 25% span. Previous measurements showed that the vortices exit the turbine blade at 50% midspan Giel et al [15]. This result is obtained by experimental measurements and confirmed by the numerical calculations.…”
Section: Grid Independence Studysupporting
confidence: 74%
“…Giel et al [15] studied the effect of Reynolds number, exit Mach number, and inlet turbulence intensity on threedimensional heat transfer using experimental measurements. The results were compared to numerical calculations using three-dimensional Navier-Stokes code.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen and Goldstein acquired their data in a blade cascade at low Reynolds numbers (120,000-170,000). Blair [9] and Giel et al [10] also reported similar high levels of heat transfer in the near endwall region of the suction surface while again their research investigated turbine rotor passages. Conversely, Harasgama and Wedlake [11] investigated transient heat transfer in an annular vane cascade and found midspan heat transfer levels were consistently higher than values near the endwall.…”
Section: Introductionmentioning
confidence: 77%
“…Hybrid unstructured grid (leading edge region) Nondimensionalized pressure on the blade surface (experimental data provided by P Giel (1999)…”
mentioning
confidence: 99%